2018
DOI: 10.18203/2349-3291.ijcp20184281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and bacteriological profile of neonatal sepsis with emerging resistance patterns

Abstract: Background: The present study was designed to evaluate the clinical spectrum, bacteriological profile, antibiotic sensitivity pattern and mortality due to neonatal septicemia in neonates admitted in neonatal units attached to the SMS Medical College, Jaipur.Methods: In born and out born babies of postnatal age up to 28 days who were bacteriological proven cases of septicemia were subjected to history, clinical examination and laboratory evaluation and data were analyzed statistically.Results: Out of 150 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
1
1
Order By: Relevance
“…In the present study, the Gram negative bacteria and Gram positive bacteria accounted for (68.3%) and (31.7%) respectively. This is in comparable with the studies done by Tak SK et al 14 , Shrestha et al 15 , Rajana R et al 16 which also showed that gram-negative organisms were more common causes of neonatal sepsis. The probable reasons being, newborns most probably acquire these Gram-negative organisms from the maternal genital tract.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the Gram negative bacteria and Gram positive bacteria accounted for (68.3%) and (31.7%) respectively. This is in comparable with the studies done by Tak SK et al 14 , Shrestha et al 15 , Rajana R et al 16 which also showed that gram-negative organisms were more common causes of neonatal sepsis. The probable reasons being, newborns most probably acquire these Gram-negative organisms from the maternal genital tract.…”
Section: Discussionsupporting
confidence: 91%
“…Neonatal sepsis was more common in neonates born in rural than in urban (70% vs 30%) similar to studies like Taller SS et al, Rasul CH et al and Iyer CR et al 5,14,15 This could be because of differences in delivery places and lack of trained knowledgeable health care providers in rural areas which may also be reason for higher incidence of sepsis in normal vs caesarean deliveries (80% vs 20%). Our study revealed that neonatal sepsis is more common in low birth babies than normal weight babies (77.5% vs 22.5%) in accordance to studies of Iyer CR et al and Rajana R et al 15,3 The could be because of immunological immaturity and overall high risk behavior of low birth neonates. Refusal of feeds and lethargy were most common symptoms of neonatal sepsis (67.5% vs 45%) consistent with Jaswal RS et al 16 The gram negative organisms were isolated in 85% of cases consistent with studies done by Mathur M et al, Rasul CH et al and Jaswal RS et al 13,14,16 The most common organisms isolated in our study were klebsiella pneumonia (40%), Escherichia coli (32.2%) and Staphylococcus aureus (15%) in that order consistent with Taller SS et al 5 The probable reason for it being that most of gram negative organisms are normal commensals and neonates are less protected against them because of low IgM antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…births according to national neonatal perinatal database. 3 According to World health organization (WHO) estimates, there are about 5 million neonatal deaths a year, with 98% occurring in developing countries. 4 The epidemiology of neonatal sepsis in developing and developed countries shows some important differences in pattern of etiological agents and their antibiotic susceptibilities.…”
mentioning
confidence: 99%
“…Pre term babies with sepsis in our study are lesser than others, 23% babies were preterm and low birth weight which is in contrast with 16 nding from Jaipur 67.3%. Pre term babies are more prone to sepsis but lesser reported in our study may be due to less sample size Antibiotic resistance pattern is varies centre to centre.…”
Section: Discussioncontrasting
confidence: 74%